Design of Web-Based Medical Record Application in the Computer Laboratory of Awal Bros University - Anisa, Desfa; Farhansyah, Fani (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
Computer technology is no longer something foreign to society, especially for those who are directly involved in the world of computers. With computer technology, data processing is much faster and easier and produces more accurate data compared to manual systems. The medical record application is an application that can manage patient data, the application contains the patient's identity, examination results, payments and other services that have been provided to the patient. Practicum in the Computer Laboratory of DIII Medical Records and Health Information Study Program, Awal Bros University is carried out every semester for students from semester I to semester V. To support student practicum activities, a medical record application is needed that students can use in the Computer Laboratory. In the Computer Laboratory of the DIII Medical Records and Health Information Study Program, there are several applications installed on each computer. However, it was felt that it was still not enough to support activities during practicum. For this reason, it is necessary to add applications to each computer so that students can better understand the use of medical record applications during the practicum. The aim of this research is to design a web-based medical record application in the Computer Laboratory of DIII Medical Records and Health Information Study Program, Awal Bros University. The application to be designed uses the PHP programming language and MySQL database